Thyroid dysfunction in human immuno-deficiency virus infected patients: a non-randomized, cross-sectional, single-center study - Mujawar, Vaheed U.; Byakod, Anilkumar C.; P. P., Lakshmi Devi; Walikar, Basavaraj N.; Usmangani, Tai A. (International Journal of Research in Medical Sciences, 2023)
Background: Increasing prevalence of thyroid dysfunction has been reported in human immuno-deficiency virus (HIV)-infected patients. However, there is insufficient evidence to recommend routine thyroid screening of asymptomatic individuals. Hence, this study was undertaken in an attempt to resolve these issues. Objectives of this non-randomized, cross-sectional, single-center study was to study thyroid function in HIV positive patients at various stages of disease. Methods: This single-center study was carried out at Al-Ameen Medical College Hospital and Government District Hospital Bijapur, Karnataka, India from December 2020 to December 2022. The final selected study population included newly diagnosed adult and adolescent (17-60 years) HIV+ patients was composed of 100 participants of either gender. Patients were interviewed and enrolled in the study after examining in detail according to the proforma and then by taking their written consent and explaining the purpose of the study. The thyroid hormone assays (S. TSH, FT3 and FT4) were done by chemiluminescence immuno assay (CLIA) using ADVIA Centaur-equipment. Results: Overall mean age was 36 years (range in years: 17–66 years) and 66 patients (66%) were males. Male: female ratio of 1.94:1 was recorded. In the 50 patients having acquired immuno-deficiency virus (AIDS), FT3 levels ranged from 0.230 to 4.0 picogram/ml with a mean of 2.131+0.9826 picogram/ml. In 50 patients having AIDS, the FT4 levels ranged from 0.30 to 1.90 nanogram/dI with a mean 1.179±0.4484 nanogram/dl. Conclusions: All forms of thyroid dysfunction were observed.